2019
DOI: 10.1038/s41598-019-47743-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulated betulinic acid analogue distinctively improves colorectal carcinoma in vitro and in vivo

Abstract: Betulinic acid, a plant secondary metabolite, has gained significant attention due to its antiproliferative activity over a range of cancer cells. A promising betulinic acid analogue ( 2c ) with better therapeutic efficacy than parent molecule to colon carcinoma cells has been reported. Despite impressive biological applications, low aqueous solubility and bioavailability create difficulties for its therapeutic applications. To overcome these lacunae and make it as a promising drug candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 58 publications
2
19
0
2
Order By: Relevance
“…Table 1 shows the physicochemical properties of JNPs. In terms of encapsulation efficiency and drug loading activities our results are compatible with similar reports in the literature (37)(38)(39).…”
Section: Discussionsupporting
confidence: 92%
“…Table 1 shows the physicochemical properties of JNPs. In terms of encapsulation efficiency and drug loading activities our results are compatible with similar reports in the literature (37)(38)(39).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, BA may induce cell apoptosis by upregulating the expression of Bax and cleaved caspase-3 and downregulating the protein expression of Bcl-2. BA may inhibit the metastasis of cancer cells, increase the production of reactive oxygen species, and reduce the mitochondrial membrane potential of cancer cells, suggesting that BA induces cancer cell apoptosis through mitochondrial-mediated pathways ( 29 ). However, the molecular mechanism through which BA achieves regulation of metabolic reprogramming and anti-CRC effects has not yet been clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis induced by in vitro antiproliferative activity was significantly increased by 2c-NP compared with the free drug (2c), and efficient depolarization of the mitochondrial membrane was observed in HT-29 cells upon increased cellular uptake of 2c-NP. Nanoencapsulation of 2c caused an appreciable decrease in cytotoxicity against normal cells in vitro and improvement of therapeutic efficacy in vivo ( 29 ). The present study also demonstrated that BA-NLs can inhibit glucose uptake and lactate secretion by CRC cells and may be involved in the regulation of glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Betulinic acid promoted the apoptosis of CRC cells and also inhibited the metastasis of cancer cells [468]. Nano-capsulated analogue (2c) with better therapeutic efficacy than parent molecule to colon carcinoma cells has been reported [469].…”
Section: Betulinic Acid (Pentacyclic Triterpenoid)mentioning
confidence: 99%